2011
DOI: 10.1007/s11250-011-9956-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ruminally protected methionine on body weight gain and growth of antlers in red deer (Cervus elaphus) in the humid tropics

Abstract: Sixteen male red deer (Cervus elaphus), with an initial weight of 93.83 ± 4.38 kg were used to study the effect of the dietary level of ruminally protected methionine (RPM) on growth, antler morphometry and serum metabolites. The deer were allowed to graze and were individually supplemented with concentrate to provide 0, 2.5, 3.5 or 4.5 g/day of RPM for 65 days. There was a quadratic effect on daily weight gain (0.163, 0.098, 0.147 and 0.172 kg/day; P < 0.005) and antler beam length (59.7, 63.6, 63.0 and 57.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…A comprehensive review [ 18 ] focusing on the supplementation of amino acids in cervids (and other ruminants) summarizes the roles of the first limiting amino acid, lysine (Lys), and methionine (Met) in the improvement of growth rates and body and reproductive development (sperm quality as well as fertility) of ruminants. For example, previous studies have shown that the supplementation of various deer species with different rumen-protected amino acids increases body weight gains [ 19 , 20 ], improves the meat yield of high-value cuts, and decreases internal fat deposition in fallow deer used for venison [ 21 ]. In breeding animals, rumen-protected amino acids have been shown to improve the sperm mass activity, motility, concentration, and membrane integrity of rams [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review [ 18 ] focusing on the supplementation of amino acids in cervids (and other ruminants) summarizes the roles of the first limiting amino acid, lysine (Lys), and methionine (Met) in the improvement of growth rates and body and reproductive development (sperm quality as well as fertility) of ruminants. For example, previous studies have shown that the supplementation of various deer species with different rumen-protected amino acids increases body weight gains [ 19 , 20 ], improves the meat yield of high-value cuts, and decreases internal fat deposition in fallow deer used for venison [ 21 ]. In breeding animals, rumen-protected amino acids have been shown to improve the sperm mass activity, motility, concentration, and membrane integrity of rams [ 22 ].…”
Section: Introductionmentioning
confidence: 99%